2010
DOI: 10.1093/rpd/ncq228
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the indoor and outdoor 220Rn (thoron) equilibrium factor: application to lung dose

Abstract: A miniature four-chamber alpha track detector was developed that measures both (222)Rn (radon) and (220)Rn (thoron), in duplicate. Using this detector and the previous long-term measurements of the (220)Rn decay products (212)Pb, and (212)Bi, an equilibrium factor, F(eq), is derived for both outdoor and indoor (220)Rn environments (0.004±0.001 outdoors and 0.04±0.01 indoors). The lung airway dose can then be calculated from a dose factor from UNSCEAR that requires the equilibrium equivalent thoron concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Instead, we observed a weaker correlation and much smaller ratios between filter-sampled 212 Pb and in situ-measured thoron, as compared to the stronger correlation and larger ratios between the integrative TnP and thoron measurements. Such low activity concentrations and equilibrium factors were also reported in another study using filter samples to assess TnP (Harley et al, 2010). One potential explanation could be a reduced filter sampling efficiency for the attached progeny of certain aerosol sizes.…”
Section: Point Measurementssupporting
confidence: 68%
“…Instead, we observed a weaker correlation and much smaller ratios between filter-sampled 212 Pb and in situ-measured thoron, as compared to the stronger correlation and larger ratios between the integrative TnP and thoron measurements. Such low activity concentrations and equilibrium factors were also reported in another study using filter samples to assess TnP (Harley et al, 2010). One potential explanation could be a reduced filter sampling efficiency for the attached progeny of certain aerosol sizes.…”
Section: Point Measurementssupporting
confidence: 68%
“…With the given constant values for D and ; the concentration of thoron at 1 m from the source should decrease to less than one percent of the initial concentration 23 . However, studies showed that the decrement is not that rapid and thoron concentration observed to drop to 10–40% at 1 m distance from the source 24 26 . The air circulation in the room promotes the thoron gas to diffuse more distance.…”
Section: Resultsmentioning
confidence: 97%
“…In the past, Rn studies were more common than those of Tn, but recent studies in Serbian [13], Chinese [4, 5], Indian [6] Canadian [79], Japanese [10], Korean [11, 12], Hungarian [13], Slovenian [14], Irish [15, 16] and USA [17] dwellings have show that Tn can be a significant contributor to the radiation exposure. The contributions of Rn and Tn and its progeny (TnP) to radiation exposure are quite different.…”
Section: Introductionmentioning
confidence: 99%